Do Gaga, Be Well?: Well-Being as Intersectional Dispositif in the Neo-spiritual Israeli Movement Practice Gaga - Aschenbrenner, Lina (New Spiritualties and the Cultures of Well-being, 2022)
With late modernity, “religion” has changed again in manifold ways its cultural shape, partly towards a preference for experiential embodied practices, health preservation, and an even closer relation to consumerist habits. The chapter explores the place of the well-being dispositif within these dynamics and further relevant framings, such as therapy culture, fitness, and health prevention, self-responsibility, self-enhancement, lifestyle aesthetization, art, and, of course, neoliberalism. A concrete example is that of the neo-spiritual Israeli and now global dance and movement practice “Gaga” that is reconstructed from data obtained in field research conducted from 2017 to 2018 at Suzanne Dellal Center in Tel Aviv—the Israeli home base of Gaga. What is illuminating in the example is the non-Christian and extra-European yet global and neoliberal context of a well-being culture, as well as the intersection of this movement practice with art. After depicting the selling-point strategy of Gaga Movement Ltd. targeting health, fitness, and coping with life, Gaga teachers’ instructions in Gaga classes together with participants’ experiences are analyzed as powerful artistic-aesthetic body techniques targeting this goal. Towards this backdrop, we question the dominance of the neoliberal framework and interpret Gaga’s particular well-being dispositif vis-à-vis other influential cultural dispositifs enumerated above. We expect that well-being culture is beyond its zenith as attention shifts away from strong, self-caring, and independent neoliberal subjects towards interdependent and vulnerable subjects.